Group cohesiveness and poly-culturalism: The study of student nomads in Malang - Diah Karmiyati; Clara Nidya Corsha; Muhammad Fath Mashuri (AMCA Journal of Community Development, 2021)
Students in Malang is derived from the background of a diverse culture. Students nomads have a community called the organization of the area. The interaction between culture is very prone to conflict and friction that a very harmful. The prevention of conflict can be done with poly-culturalism or the belief that each group has interact with each other and provide a positive influence. But the cohesiveness of the group owned by a regional organization as the internal strength of the group can be a barrier in the relationship between the organization of the area. The purpose of this study is to determine whether there is a correlation between group cohesiveness with poly-culturalism on student nomads in Malang. This research is a quantitative research, using purposive sampling techniques. The research instrument used the Group Cohesiveness Scale and Poly-culturalism Scale. The results showed that there is a positive significant relationship between group cohesiveness and poly-culturalism on student nomads in Malang. Group cohesiveness which is owned by the students of the nomads in Malang does not inhibit the formation of poly-culturalism.